Voicing the Voids: The Burdens of Translation (Spectrum, 2022)
Using a diverse array of translation theory, this essay re-presents the task of a South Asian translator in terms of their presence, absence, and existence within the voids of translation and untranslativity of languages. In its exploration of translation theory, the essay uses Nawab Faizunnesa’s Rupjalal and Neelima Ibrahim’s Ami Birangona Bolchi, and examines how the translator addressed the issues of creative obligation and translative/academic autonomy in translating these two iconic texts.Spectrum, Volume 16, June 2021: 127-135